Potentially inappropriate prescribing in institutionalised older patients in Spain: the STOPP-START criteria compared with the Beers criteria - Bonet M; Peris JE; Gomez C; Ferrándiz ML; Maicas N; Ubeda A (Centro de Investigaciones y Publicaciones Farmaceuticas, 2012)
Objective: The aims of this study were to identify potentially inappropriate prescribing using the Beers and STOPP criteria. The START criteria were applied to detect prescription omission in the geriatric population. We compared the utility of these criteria in institutionalised older people.Methods: Descriptive study reviewing the medication and clinical records of 81 residents (aged 65 years and more) by pharmacists in a nursing home in the Lleida region (Spain).Results: The mean patients' age was 84 (SD=8) years, with an average of 5 drugs per resident (total prescriptions: 416 medicines). The Beers criteria identified potentially inappropriate medication use in 25% of patients and 48% of patients used at least 1 inappropriate medication according to STOPP criteria. The most frequent potentially inappropriate medications for both criteria were long-acting benzodiazepines and NSAIDs. START detected 58 potential prescribing omissions in 44% of patients. Calcium-vitamin D supplementation in osteoporosis was the most frequent rule (15%), but omissions corresponding to the cardiovascular system implied 23% of patients.Conclusion: The STOPP-START criteria reveal that potentially inappropriate prescribing (PIP) is a highly prevalent problem among Spanish nursing home residents, and a statistically significant positive correlation was found between the number of medicines prescribed and the number of PIP detected in this study. The STOPP criteria detect a larger number of PI medications in this geriatric population than the Beers criteria. The prescribing omissions detected by the START criteria are relevant and require intervention. Pharmacists' review of medications may help identify potentially inappropriate prescribing and, through an interdisciplinary approach, working with physicians may improve prescribing practices among geriatric residents of nursing homes.